Implementasi Pembelajaran Kitab Ta’lim Al-Muta’alim Dalam Membentuk Karakter Murid Di MTS Arriyad Desa Sukamurni - Sudirman Sudirman (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2023)
Slowly the teacher's ethics are getting further away from the afterlife. Therefore, the procedures for studying need to be reopened so that students do not fall further. The thoughts of Sheikh Az-Zarnuji in the book Ta'lim Al-Muta'allim can be used as an alternative solution to this problem. Therefore, this book is taught in educational institutions, namely schools which include: conceptualizing learning activities, implementing learning concepts, and supporting and inhibiting factors in learning the book of Ta'lim Al-Muta'allim. The research was conducted in MTs. Ariyad. This research uses qualitative research, case study type, using descriptive method. Researchers act as implementers, full observers, as well as data collectors, and the presence is known as a researcher. Data collection is done by interview, observation, and documentation. The research informants were principals, teachers and students in each research location. The data obtained were then analyzed using the Miles and Humberman interactive analysis technique. Meanwhile, checking the validity of the data is carried out with credibility, transferability, dependability, and confirmability. Furthermore, the results of the research are: 1) conceptualizing the learning of the book of Ta'lim Al-Muta'allim done by examining the basic things that become the foundation of learning, including: reviewing the contents of the book, formulating goals, identifying resources, designing learning. 2) implementing the concept of learning activities for the book of Ta'lim Al-Muta'allim, including: controlling the performance of school principals and teachers, seeing the condition of students and learning tools, correcting learning methods, and maintaining the motivation of all those involved in the learning process with interactive communication methods . 3) supporting and hindering factors for implementing the concept of learning activities in the book of Ta'lim Al-Muta'allim supporting factors, including: adequate facilities and infrastructure, learning materials, and teachers who teach. Inhibiting factors include: the limited ability of students, and the limited experience of the teacher.